2018
DOI: 10.1037/emo0000320
|View full text |Cite
|
Sign up to set email alerts
|

Children’s and mothers’ cardiovascular reactivity to a standardized laboratory stressor: Unique relations with maternal anxiety and overcontrol.

Abstract: Research documents bidirectional associations between parental overcontrol (OC) and children's anxiety; OC may place children at risk for anxiety and also may occur in response to children's requests for help. However, to date no studies have examined children's or parents' in-the-moment emotional responses to OC. Using a community sample of mothers and school-age children, we examine the individual and interactive influences of maternal OC, maternal anxiety, children's help-seeking, and children's anxiety in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…We coded parental OC from the 15‐minute triadic family discussion. Our observational coding system was adapted from existing scales for measuring OC (Hudson & Rapee, ; Siqueland, Kendall, & Steinberg, ; Whaley, Pinto, & Sigman, ) and mirrors other behavioral measures of OC in middle childhood (e.g., Borelli, Burkhart, Rasmussen, Smiley, & Hellemann, ). Coders rated the extent to which the parent attempted to constrain or control the child's behaviors, cognitions, or emotions.…”
Section: Methodsmentioning
confidence: 99%
“…We coded parental OC from the 15‐minute triadic family discussion. Our observational coding system was adapted from existing scales for measuring OC (Hudson & Rapee, ; Siqueland, Kendall, & Steinberg, ; Whaley, Pinto, & Sigman, ) and mirrors other behavioral measures of OC in middle childhood (e.g., Borelli, Burkhart, Rasmussen, Smiley, & Hellemann, ). Coders rated the extent to which the parent attempted to constrain or control the child's behaviors, cognitions, or emotions.…”
Section: Methodsmentioning
confidence: 99%
“…The modality of delivery also matters. Emotion inductions that use film clips often result in increases in RSA (Alkon et al, ; Davis et al, ; Hastings, Klimes‐Dougan, Kendziora, Brand, & Zahn‐Waxler, ; Quigley & Stifter, ), which contrasts with patterns observed during naturalistic inductions (like an impossible or frustrating task), which often elicit physiological arousal (Borelli, Burkhart, Rasmussen, Smiley, & Hellemann, ; Hastings et al, ; Perry, Calkins, Nelson, Leerkes, & Marcovitch, ). Using measures of RSA across four emotion contexts, Gaztke‐Kopp and Ram () showed that emotion context‐level physiological change explained a small but unique proportion of the variance in children's RSA scores.…”
Section: Temporally Moderate Contexts Of the Psychobiology Of Self‐rementioning
confidence: 99%
“…Analyses of data not reported here indicate that for the sample as a whole, children's self‐reported negative emotion increased and RSA decreased from baseline in response to the stressor (see Borelli, Burkhart, Rasmussen, Smiley, & Helleman, ; Borelli, Vazquez, et al, ), suggesting that the task evoked a stress response.…”
Section: Resultsmentioning
confidence: 74%
“…Third, although the present study is interested in emotion regulation processes, we aimed to use the PANAS and the SAM to measure children's emotional state during the PCT; however, given that children only completed these inventories at baseline and immediately after the conclusion of the puzzle tasks-when they may have already begun to calm down from the stressful experience-it is plausible that this assessment method captured children's ability to regulate their emotion reactivity, rather than their exact levels of frustration during the task. However, although we cannot guarantee that emotion regulation did not have some impact on children's emotion ratings, the fact that children's negative emotion increased from baseline to poststressor (see Borelli, Burkhart, et al, 2017;Borelli, Vazquez, et al, 2016) enhances our confidence that this methodology allowed us to at least partially capture children's emotion reactivity. Moreover, we note that theorists contend that emotion can be regulated before it occurs (e.g., Gross, 1998).…”
Section: M Itati O N Smentioning
confidence: 94%